Effects of adenosine A1 receptor antagonism on insulin secretion from rat pancreatic islets - Zywert, A; Szkudelska, K; Szkudelsky, T (Physiological research, 2011)
Adenosine is known to influence different kinds of cells, including β-cells of the pancreas. However, the role of this nucleoside in the regulation of insulin secretion is not fully elucidated. In the present study, the effects of adenosine A1 receptor antagonism on insulin secretion from isolated rat pancreatic islets were tested using DPCPX, a selective adenosine A1 receptor antagonist. It was demonstrated that pancreatic islets stimulated with 6.7 and 16.7 mM glucose and exposed to DPCPX released significantly more insulin compared with islets incubated with glucose alone. The insulin-secretory response to glucose and low forskolin appeared to be substantially potentiated by DPCPX, but DPCPX was ineffective in the presence of glucose and high forskolin. Moreover, DPCPX failed to change insulin secretion stimulated by the combination of glucose and dibutyryl-cAMP, a non-hydrolysable cAMP analogue. Studies on pancreatic islets also revealed that the potentiating effect of DPCPX on glucose-induced insulin secretion was attenuated by H-89, a selective inhibitor of protein kinase A. It was also demonstrated that formazan formation, reflecting metabolic activity of cells, was enhanced in islets exposed to DPCPX. Moreover, DPCPX was found to increase islet cAMP content, whereas ATP was not significantly changed. These results indicate that adenosine A1 receptor blockade in rat pancreatic islets potentiates insulin secretion induced by both physiological and supraphysiological glucose concentrations. This effect is proposed to be due to increased metabolic activity of cells and increased cAMP content.
Keywords: receptor adenosinový A1; xanthiny; Cyclic AMP; inzulin; Langerhansovy ostrůvky; AMP cyklický; Adenosine A1 Receptor Antagonists; Xanthines; Rats, Wistar; Receptor, Adenosine A1; Rats; Adenosine Triphosphate; antagonisté adenosinového receptoru A1; potkani Wistar; Dose-Response Relationship, Drug; zvířata; adenosintrifosfát; krysa rodu Rattus; Islets of Langerhans; Insulin; Animals